2005
DOI: 10.1111/j.1365-2818.2005.01444.x
|View full text |Cite
|
Sign up to set email alerts
|

Radon track imaging in CR‐39 plastic detectors using confocal scanning laser microscopy

Abstract: SummaryConfocal scanning laser microscopy (CSLM) has been used to provide the first images of radon track populations in two external CR-39 plastic detectors. Measurements of variables including track area distribution and estimates of the angle of track inclination (dip) derived from surface CSLM sections are presented. CSLM depth slices, combined with three-dimensional (3D) visualization techniques, provide a new, non-destructive way of examining the 2D and 3D geometry of the etched tracks within solid-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Some tracks may be at an angle resulting in variation in grey levels seen in microscopy (Nikezic & Yu, 2008). Our study extends earlier work (Petford et al , 2005) which was aimed at classifying and quantifying the shape, size, area and angular distribution of nuclear tracks in solid‐state detectors. Such analysis forms the basis of the fission track dating method (Wagner & van der Haute, 1992).…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Some tracks may be at an angle resulting in variation in grey levels seen in microscopy (Nikezic & Yu, 2008). Our study extends earlier work (Petford et al , 2005) which was aimed at classifying and quantifying the shape, size, area and angular distribution of nuclear tracks in solid‐state detectors. Such analysis forms the basis of the fission track dating method (Wagner & van der Haute, 1992).…”
Section: Introductionsupporting
confidence: 78%
“…It is important to note that there can be some variation in reported results, even in closely spaced detectors (Cliff & Gillmore, 2001), due in part to error margins in measurement equipment or techniques. We have previously observed that radon tracks in CR‐39 detectors can be visualized using confocal microscopy and hence information about 3D track geometry can be obtained (Petford et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described confocal microscopy methods to obtain 3-D data for particle track visualisation and analysis (Petford et al, 2005;Wertheim et al, 2009). Although 3-D imaging of the tracks could be more timeconsuming than 2-D analysis, 3-D analysis has the potential to provide information relating to angle at which the alpha particle hits the detector as well as possibly indicating the energy of alpha particles.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally etched SSNTDs are assessed using 2D microscope imaging. Confocal microscopy can be used to obtain 3D image datasets of tracks in SSNTDs (Petford et al, 2005;Hermsdorf & Hunger, 2009). Fluorescent confocal microscopy was used to image SSNTDs by treating the detectors with Nile Blue A (Hermsdorf & Hunger, 2009).…”
Section: Ssntd Imagingmentioning
confidence: 99%
“…Fluorescent confocal microscopy was used to image SSNTDs by treating the detectors with Nile Blue A (Hermsdorf & Hunger, ). We have previously used the LEXT OLS 3100 confocal microscope to successfully image CR‐39 radon track detectors (Petford et al ., ; Wertheim et al ., , b). These studies used reflection confocal microscopy to enable 3D visualisation and quantification of tracks from surface data and without the need for using a fluorescent dye.…”
Section: Introductionmentioning
confidence: 99%